Honduras : Joint Staff Assessment of the Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report, 2005)
The paper discusses the Joint Staff Assessment (JSA) of the Poverty Reduction Strategy Paper (PRSP) Progress Report for Honduras. The first PRSP Progress Report of the Government of Honduras presents a complete review of the government's implementation of the PRSP to date and updates the PRSP for 2004-07. The report presents a comprehensive assessment of challenges encountered in implementing the poverty reduction strategy in Honduras. It reports on progress made to date and candidly identifies factors related to less-than-satisfactory Poverty Reduction Strategy implementation.